Utilazation of Bamboo as Non-Timber Forest Products (NFTPs) by Kalaodi Villagers in the Indonesian Island of Tidore - Baguna, Firlawanti Lestari; Marasabessy, Much. Hidayah (Cannarium, 2020)
Kalaodi is one of the villages in Tidore Isle which is located around the Tagafura protected forest and has a diverse diversity of non-timber forest products (NTFPs). Bamboo as NTFPs has been commonly used by the Kalaodi Community in daily life such as building materials, food containers, materials for traditional ceremonies or traditional games. The study aims to identify the types of bamboo in Kalaodi and to know the utilization of bamboo. Data retrieval is done through observation and interviews with informants. The selection of informants used a quota-based snowball sampling method. Selected informants were traditional leaders, communities, bamboo farmers, and the community as many as 30 informants. The results showed that 7 (seven) types of bamboo were utilized by the community around the Kalaodi Village forest area, namely Tabaliku Cina, Lou, Tui Biasa, Tabaliku Ake, Gilou, Lou Van, Lou Van, and Tui Jawa. Utilization of bamboo by the community Kalaodi as building materials, furniture, craft materials, social-cultural activities, and environment.